Penyuluhan Pencegahan Stunting Sejak Dini Di Desa Kota Lama - Aref Vai; Rameilisa Karita; Nurakma Hani; Dea Apriana; Tri Wahyu Darma; Preldi Chandra Murti; Figo Fahcrezi; Inne Triyanda; Azra Salsabila; Muhammad Alfhat Ramadhan; Novirawil Fitri (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2023)
Stunting is one of the nutritional problems as well as a serious threat To children in Indonesia. Currently, the stunting rate in Indonesia is 37.2% or equivalent to 8 million children with suboptimal Growth. This is behind our need to hold a stunting counseling Program, especially in Simpang Roda (III) hamlet, Kota Lama village, Rengat Barat district, Indragiri Hulu Regency. The form of counseling is in the Form of providing information services by collaborating with local Posyandu cadres to convey information to the community to invite The community to carry out public health movements. The hope is That the holding of stunting counseling activities in Kota Lama village can increase public awareness regarding the importance of Child growth and development so that increasingly noticed and Increasing, so as to prevent stunting and reduce the percentage of Stunting in Indonesia, especially in Simpang Roda (III) hamlet, Kota Lama village, Rengat Barat District, Indragiri Hulu Regency.